2023
DOI: 10.3390/ma16134860
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Full-Scale UHPC-Filled Steel Tube Composite Columns under Axial Load

Abstract: In the realm of civil engineering, ultra-high-performance concrete-filled steel tube composite columns (UCFSTCs) constitute a new type of building material and structure, exhibiting high compressive strength and commendable durability. Given their promising characteristics, the prospects of their application are highly promising and are worthy of further exploration. However, current research has primarily focused on scaled-down specimens, thereby limiting a broader understanding of UCFSTCs’ full-scale mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Cheng et al [31] utilised ultra-high-performance concrete-filled steel tube composite columns to exhibit high compressive strength and durability. The findings suggested that increasing steel tube strength and thickness significantly improved the ultimate bearing capacity while reducing the ductility coefficient.…”
Section: Concrete-filled Steel Tubular Columnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al [31] utilised ultra-high-performance concrete-filled steel tube composite columns to exhibit high compressive strength and durability. The findings suggested that increasing steel tube strength and thickness significantly improved the ultimate bearing capacity while reducing the ductility coefficient.…”
Section: Concrete-filled Steel Tubular Columnsmentioning
confidence: 99%
“…Additionally, increasing the concrete strength enhanced the ultimate bearing capacity but decreased the ductility coefficient. Their study also evaluated the contribution of concrete to the overall load-bearing capacity of the composite columns, indicating the significant role of concrete in the load-carrying capacity of the composite columns [31]. CFST composite columns are widely used in construction because they can sustain heavy loads with high performance.…”
Section: Concrete-filled Steel Tubular Columnsmentioning
confidence: 99%